The effectiveness of chemical fungicides and plant extracts to inhibit the mycelial growth of phytophthora palmivora causing black pod disease on cocoa / Nur Alia Mohammed Baharudin - Mohammed Baharudin, Nur Alia (Faculty of Plantation and Agrotechnology, 2018)
Black pod diseases caused by Phytophthora palmivora have become a major impediment in the cocoa production in Malaysia. The pathogen could reduce the fruit weight and severe infection will reduce the yield and also fruit quality. The objectives of the study were to determine the most effective fungicide and plant extract an biocontrol agent to inhibit the growth of P. palmivora using In-vitro study. In this study, systemic fungicides namely benomyl and metalaxyl and non systemic fungicide, mancozeb were used. Meanwhile, ginger (Zingiber offiicinale), lemongrass (Cymbopogon nardus) and garlic (Allium sativum) were used as biological control agents. The fungicides were tested using poison food technique with concentration at 1000 ppm. Based on the results, mancozeb and metalaxyl were effective to inhibit the mycelial growth of P. palmivora. While, benomyl was not effective. For the biological control agents, garlic was effective to inhibit the mycelial growth of P. palmivora. While, ginger and lemongrass were not effective.